Dietary protein and blood pressure: a systematic review. - Wieke Altorf-van der Kuil; Mariëlle F Engberink; Elizabeth J Brink; Marleen A van Baak; Stephan J L Bakker; Gerjan Navis; Pieter van 't Veer; Johanna M Geleijnse (PLoS ONE, 2010)
Background Elevated blood pressure (BP), which is a major risk factor for cardiovascular disease, is highly prevalent worldwide. Recently, interest has grown in the role of dietary protein in human BP. We performed a systematic review of all published scientific literature on dietary protein, including protein from various sources, in relation to human BP. Methodology/principal findings We performed a MEDLINE search and a manual search to identify English language studies on the association between protein and blood pressure, published before June 2010. A total of 46 papers met the inclusion criteria. Most observational studies showed no association or an inverse association between total dietary protein and BP or incident hypertension. Results of biomarker studies and randomized controlled trials indicated a beneficial effect of protein on BP. This beneficial effect may be mainly driven by plant protein, according to results in observational studies. Data on protein from specific sources (e.g. from fish, dairy, grain, soy, and nut) were scarce. There was some evidence that BP in people with elevated BP and/or older age could be more sensitive to dietary protein. Conclusions/significance In conclusion, evidence suggests a small beneficial effect of protein on BP, especially for plant protein. A blood pressure lowering effect of protein may have important public health implications. However, this warrants further investigation in randomized controlled trials. Furthermore, more data are needed on protein from specific sources in relation to BP, and on the protein-BP relation in population subgroups.